2018
DOI: 10.1051/0004-6361/201832666
|View full text |Cite
|
Sign up to set email alerts
|

Particle acceleration in the superwinds of starburst galaxies

Abstract: Context. Starbursts are galaxies undergoing massive episodes of star formation. The combined effect of stellar winds from hot stars and supernova explosions creates a high-temperature cavity in the nuclear region of these objects. The very hot gas expands adiabatically and escapes from the galaxy creating a superwind which sweeps matter from the galactic disk. The superwind region in the halo is filled with a multi-phase gas with hot, warm, cool, and relativistic components.Aims. The shocks associated with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 103 publications
1
69
0
8
Order By: Relevance
“…The sound speed in the hot wind regions present in typical starbursts is about 100 km s −1 (Romero et al 2018). Hence the sonic Mach number turns out to be ∼12.…”
Section: Shock Compression At the Boundaries Of Anmentioning
confidence: 96%
“…The sound speed in the hot wind regions present in typical starbursts is about 100 km s −1 (Romero et al 2018). Hence the sonic Mach number turns out to be ∼12.…”
Section: Shock Compression At the Boundaries Of Anmentioning
confidence: 96%
“…11, the maximum energy attainable by iron nuclei entering into the electrostatic gap of the black hole magnetosphere would be ∼ 2×10 15 eV. This is even less than what Romero et al (2018) estimated for particle acceleration in the superwind. If NGC 253 and other starbursts are confirmed as sources of UHECRs of high metalicity, then the cosmic rays should probably be originated in compact , for different values of the magnetic field intensity.…”
Section: Cosmic Raysmentioning
confidence: 81%
“…4 × 1. 0, there is some room for contributions from the base of the superwind as suggested by Romero et al (2018). GeV gamma rays might also be produced in the superwind, but Fermi resolution does not allow to disentangle this radiation if present.…”
Section: Different Contributions To Gamma Raysmentioning
confidence: 99%
“…Recently, ALMA interferometer showed that the mass loading factor of NGC 253 is very high: β ∼ 12 [17]. Table 1 in [18] presents a summary of the physical properties of NGC 253.…”
Section: Ngc 253 and Cosmic Raysmentioning
confidence: 99%